2008
DOI: 10.1021/jf802832w
|View full text |Cite
|
Sign up to set email alerts
|

Olean-27-carboxylic Acid-Type Triterpenes with Potent Antibacterial Activity from Aceriphyllum rossii

Abstract: Aceriphyllum rossii Engler (Saxifragaceae) have been used as a nutritious food in Korea. We found that the methanol extract of the root portion of A. rossii potently inhibited the growth of Staphylococcus aureus , with a minimal inhibitory concentration (MIC) value of 8 microg/mL. Using mass spectrometry and nuclear magnetic resonance (NMR) studies, four active constituents were isolated and identified: aceriphyllic acid A, 3-oxoolean-12-en-27-oic acid, 3alpha-hydroxyolean-12-en-27-oic acid, and 3beta-hydroxyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…The roots of A. rossii contain oleanane-type triterpenoids, which are cytotoxic to MCF-7 and LLC cancer cells, 4) acyl-CoA-cholesterol Oacyltransferase inhibition and antibacterial activity. 5,6) Inhibition of protein tyrosine phosphatase 1B activity by triterpenes isolated from the seeds of A. rossii has also reported. 7) In addition, flavonoids isolated from the aerial parts showed antioxidant activity.…”
Section: )mentioning
confidence: 95%
“…The roots of A. rossii contain oleanane-type triterpenoids, which are cytotoxic to MCF-7 and LLC cancer cells, 4) acyl-CoA-cholesterol Oacyltransferase inhibition and antibacterial activity. 5,6) Inhibition of protein tyrosine phosphatase 1B activity by triterpenes isolated from the seeds of A. rossii has also reported. 7) In addition, flavonoids isolated from the aerial parts showed antioxidant activity.…”
Section: )mentioning
confidence: 95%
“…This result was confirmed for the reference strain, Enterococcus faecalis ATCC 28212 [21] (Table 1). Olean-27-carboxylic acid-type triterpenes extracted from the root portion of Aceriphyllum rossi (Saxifragaceae) which is a staple food in Korea, exhibited potent antibacterial activity against several strains of MRSA (methicillin-resistant S. aureus) and quinolone-resistant Staphylococcus aureus [29]. This result indicated that both the carboxylic group at C-27 and the hydroxyl group at C-24 in aceriphyllic acid A are critical for the strong bactericidal activity.…”
Section: Antibacterial Activity Of Oa and Its Derivativesmentioning
confidence: 99%
“…21,22) Our recent study demonstrated that a triterpene 3-oxoolean-12-en-27-oic acid (3-OA) isolated from A. rossii induced apoptosis in HL-60 cells through the caspase-8-mediated extrinsic pathway. 12) In the present study, we investigated the anti-cancer activity of another triterpene 3a,23-isopropylidenedioxyolean-12-en-27-oic acid (IPA) isolated from A. rossii and its underlying mechanism in HeLa cells.…”
Section: Fig 4 Effect Of Ipa On Er Stress-mediated Apoptosis In Helmentioning
confidence: 99%